Is Equality Stable? - Mookherjee, Dilip; Ray, Debraj (American Economic Review, 2002)
Economic inequality is of interest not only at some intrinsic level, but also for its close connections to diverse variables, ranging from economic indicators such as growth rates to sociopolitical outcomes such as collective action and conflict.It is only natural, then, to study the evolution of inequality in an economic system.It is fair to say that the dominant view on this topic is that inequality is the outcome of a constant battle between convergence and "luck" (Gary Becker and Nigel Tomes, 1979).Current asset inequalities may echo into the future, but their natural tendency is to die out (owing to a convex investment technology).Disparities are only sustained through ongoing stochastic shocks (see also David Champernowne, 1953;Glenn Loury, 1981).A second approach emphasizes that initial conditions determine final outcomes, owing principally to a nonconvex investment technology (see e.g.